Experience in the application of laparoscopic appendectomy in acute appendicitis - S. N. Zavgorodniy; А. І. Rylov; М. А. Kubrak; М. В. Danyluk; O. D. Naydenov; G. M. Grishchenko (Patologìâ)
Laparoscopic appendectomy is the gold standard in the treatment of patients with acute appendicitis.